" History Speaks Our Language!" A Comparative Study of Historical Narratives in Soviet and Post-Soviet School Textbooks in the Caucasus (2007)
Long before the demise of the USSR, Western Sovietologists had noted the fact that in the Soviet Union the official version of history changed frequently. However, there is something that has passed almost unnoticed by the majority of scholars; namely, the debate about which version of history should be considered as true, and accepted as the official version to be included in school textbooks in the Soviet autonomous republics. This paper deals with several aspects of this process and its legacy by examining the way in which the distant past is presented in Soviet and post-Soviet school history textbooks. The author reveals the conflicting ethnic historical narratives in the textbooks of rival ethnic groups, focusing on the use of linguistic arguments to link ethnic identity to the territory controlled by the ‘titular’ ethnic group, and on the justification of the historical legitimacy of claims to territories by neighboring rival ethnic groups.